The Persuasive Use of Emotions. (July 2019) - Dow, Jamie
Abstract: The rhetorical power of emotions came to philosophers' attention early on in the Western tradition: emotions can exert a powerful effect on what an audience comes to believe or decides to do. It is has been surprisingly neglected since, despite abundant philosophical literature on the emotions. This paper focuses on the mechanisms and propriety of emotional persuasion. Our central focus is an apparent tension between two claims. ('PROPRIETY') Persuasion should succeed by getting people convinced on grounds that contribute to justifying their inclination to favour what the speaker proposes; and ('ANTI-AUSTERITY') It is not required that persuasion's methods be dispassionate. They seem in tension, and yet dropping either seems unattractive. In particular, dropping 'ANTI-AUSTERITY' could commit us to a position that tends to elevate further in public deliberation the contributions of already privileged voices, and to marginalise the less privileged. This paper highlights what we would need to believe, in order to hold these two claims together. In order for emotions to contribute to (epistemic) justification, I argue, they must be capable themselves of being epistemically justified, and of transmitting that epistemic justification to the beliefs to which they help give rise. This in turn requires that emotions have representational contents, involve the subject's accepting those contents as true, be candidates for epistemic justification, and be such that their contents can properly feature as premises in inferences that justify the subject in believing their conclusions. Such are the striking philosophical implications of some everyday observations about the persuasive use of emotions.